The Cortical Localization of Language and the “Birth” of the Cognitive Neurosciences - Carmela Morabito (Rivista Internazionale di Filosofia e Psicologia, 2013)
Whereas at the beginning of the XIXth century, Gall’s description of “heads” received little scientific attention, by the end of the century, the cortical maps produced by the “cerebral cartography” of Ferrier were considered a true reproduction of the actual positions of the cortical functions. Gall conceived the brain as a mass of “organs”, each constituting a specific instrument of an equally specific “faculty” of the soul. Ferrier, by contrast, considered the brain as a unitary organ made up of specific sensory and/or motor functional centres and of “associative” areas responsible for the more complex and integrated aspects of animal and human behaviour. Building on the clinical work of Broca and Jackson, the localizationistic model, supported by Ferrier’s experimental evidences and clinical data, made it possible to replace the old neurological model with a new model for understanding the relation between the nervous system and behavior. Gall had wanted to put forward a new idea about the brain and mind, but he could only proffer a “speculative” theory devoid of clinical and experimental support in support of this idea. By the end of the century, however, the cognitive neurosciences had found their new paradigm: every mental function was considered to arise from motion and sensation, and from the integrative action of the nervous system.